Early evidence for pig domestication (8,000 cal. BP) in the Lower Yangtze, South China - Jiajing Wang; Yiyi Tang; Yunfei Zheng; Leping Jiang; Xiaolin Ma; Yanfeng Hou; Guoping Sun (Proceedings of the National Academy of Sciences, 2025)
The domestication of pigs ( Sus scrofa ) has had profound socioeconomic and ecological consequences. Although pigs are believed to have been independently domesticated in South China, the timing and initial mechanisms of this process remain debated. This study presents a microfossil analysis of pig dental calculus from two early Neolithic sites in the Lower Yangtze River region: Jingtoushan (8,300 to 7,800 cal. BP) and Kuahuqiao (8,200 to 7,000 cal. BP). Analyses of starch, phytolith, and parasite remains indicate that pigs consumed human-associated foods and waste, including cooked starchy plants and human whipworm ( Trichuris trichiura ) eggs, likely derived from food preparation and fecally contaminated materials. Identified plant taxa include acorns (Fagaceae), rice ( Oryza sp.), underground storage organs such as yam ( Dioscorea sp.), and wild grasses (Triticeae and Panicoideae), all present in the local botanical assemblages. Coefficients of variation in dental metrics further indicate the coexistence of both domestic and wild populations. Together, these lines of evidence point to multiple modes of human–pig interaction, including early domestic pigs under human management, pigs scavenging near settlements, and free-ranging individuals foraging beyond human influence. Pig domestication in the Lower Yangtze had begun by 8,000 y ago, likely following both commensal and prey pathways, in parallel with the development of rice cultivation and sedentary lifeways. This study also demonstrates the value of dental calculus analysis for revealing early human–animal relationships before the appearance of clear morphological markers of domestication in the archaeological record.